PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO A LA JUNTA DE RIEGO DEL SISTEMA CAMPANA MALACATOS - Guamán Medina, Mario Andrés (2019)
The present research work is based on the search for new growth opportunities to improve the economy and quality of life of the members of the Campana Malacatos System Irrigation Board and their families through voluntary organization, eradicating informal financial operations, allowing a greater generation of economic resources within the sector; generating economic profitability in their investments, financial returns as an additional income for their members through the placement of loans with accessible interest rates and amounts appropriate to the reality of the sector, contributing with these in their agricultural activities. This work has been developed based on the established structure of a feasibility study as such, starting with a market study, as well as a technical study, legal administrative and finally a financial study, which allowed to evaluate the project. In order to fulfill the first objectives, the market study was carried out with a survey directed to the members of this organization, which determined the acceptability of the savings bank and its products, i.e. the unsatisfied demand that exists within the organization, which can be used to carry out this project, Through the technical study the location and adequate size of the project was determined, it also allowed to identify the installed capacity and used in the granting of its products, in addition the necessary elements for the operation of the box, determining the location, in the office of the Board located in the center of the parish, in the legal study was determined the organizational structure of the Savings Bank "JUNTA DE RIEGO.S.C.M" in the same one determined the functions and responsibilities of the personnel of work, on the other hand, a legal statute of the box was designed to which all partner must be governed, this statute must be always to watch of the SEPS, within the financial study or financial evaluation, the value of the fixed assets, deferred assets and the capital of work was determined, in short, the total of the necessary investment so that the savings bank works correctly. In the same way, it was possible to determine the feasibility of the project through financial indicators such as Net Present Value, Internal Rate of Return, Benefit Cost Ratio and Capital Recovery Period, as well as in the conclusions and recommendations where it was determined that the project is feasible according to the results obtained through this entire research process.